Scaling Up Innovation - Exemplary Initiatives for Sustainable Development in European Smart Cities with a Focus on Smart Mobility - Derlukiewicz, Niki; Szałata, Łukasz; Mańkowska, Dominika (European Journal of Sustainable Development, 2023)
The development of a sustainable economy is the goal of the whole society in the European Union. With over half of the global population residing in urban areas, the significance of building resilient cities cannot be overstated. Cities are at the forefront of driving adaptation and building resilience implementing ambitious strategies and activities to effectively cope, adapt, and transform, considering three pillars of sustainable development: economic growth, environmental management and social inclusion. This study explores the toolbox of best practices - activities and innovations that European cities are implementing to achieve sustainable development goals. In the article, the best practices and innovative approaches that cities are taking toward sustainability were identified. This article explores the key aspects of smart mobility and its potential to reshape urban transportation systems for a more sustainable future. The findings in the paper indicate that European cities are making significant efforts to adopt sustainable practices, including investments in renewable energy, green infrastructure, public transportation, waste management, and sustainable urban planning. The study highlights the importance of the need for inter-sectoral collaborations to achieve SD goals. The insights gained from this study can inform policy-making and assist cities in developing effective strategies for sustainable development. Keywords: smart city, innovation, sustainable development, urban development, smart mobility